KAJIAN TERHADAP EFEKTIVITAS PENEGAKAN HUKUM TINDAK PIDANA PEMALSUAN BUSI MEREK NGK MENURUT UNDANG-UNDANG 15 TAHUN 2001 (Studi Di Kota Pontianak) - FACHRIO OKTIANDA HARAHAP, SH. A.21210055, Jurnal Mahasiswa S2 UNTAN (Jurnal NESTOR Magister Hukum, 2014)
AbstractThis thesis is Studies of Effectiveness Straightening Of Forgery Crime Law of Brand Spark Plug NGK According To Law Number 15, 2001 (Study In Pontianak City). By the legal and social legal reseach method, obtained conclusion that : 1. There are some primary factors, what causes straightening of forgery crime law of spark plug Merek NGK in Pontianak City is less effective, that is: a. Section 90 until Section 94 Law Number 15, 2001 About Brand, essentially doesn't arrange in concreete about crime